Financial Policymaking after Crises: Public vs. Private Interests - Orkun Saka; Yuemei Ji; Paul De Grauwe (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We first present a simple model of post-crisis policymaking driven by both public and private interests. Using a novel dataset covering 94 countries between 1973 and 2015, we then establish that financial crises can lead to government interventions in financial markets. Consistent with a public interest channel, we find post-crisis interventions occur only in democratic countries. However, by using a plausibly exogenous setting -i.e., term limits- muting political accountability, we show that democratic leaders who do not have re-election concerns are substantially more likely to intervene in financial markets after crises, in ways that may promote (obstruct) private (public) interests.
Keywords: G01; G28; P11; P16; 330; financial crises; reform reversals; democracies; term-limits; special-interest groups